Repercussões da exposição materna ao antidepressivo venlafaxina sobre o desenvolvimento mamário e ovariano na prole de fêmeas wistar - Altieri, Marcelo Augusto [UNESP] (2025)
The chronic use of selective serotonin reuptake inhibitors or serotonin-norepinephrine reuptake inhibitors (SNRIs) may result in human gynecomastia, mamoplasia, galactorrhea, and elevated breast cancer risk. As antidepressants are frequently used for postpartum depression (PPD) treatment, this study investigated the adverse effects of lactational exposure to venlafaxine (VENL, a selective SNRI) on mammary gland development and carcinogenesis in F1 female offspring. Thus, lactating Wistar rats (F0) received VENL by oral gavage at daily doses of 3.85, 7.7, or 15.4 mg/kg (N = 9, each group) from the lactational day (LD 1) until the weaning of the offspring (LD 21). F1 female offspring were euthanized for mammary gland, and ovary histological analyses on the post-natal day (PND) 22 and 30 (1 pup/litter/period, N= 9, each group). At PND 22, other females (2 pups/litter) received a single dose of carcinogen N-methyl-N-nitrosourea (MNU, 50 mg/kg) intraperitoneally (i.p.) for tumor susceptibility assay until PND 250. Tumor incidence and latency were recorded and representative tumor samples were collected for histopathology. The results indicate that lactational exposure to VENL did not alter the development of the mammary gland (epithelial ductal tree or the mean number of terminal end buds), or the ovary (weight and primary, secondary, tertiary, and Graafian follicles) in prepubertal F1 female offspring. In addition, VENL exposure did not influence tumor incidence or tumor latency in adult female offspring who received MNU. Thus, the findings of this animal study indicated that lactational VENL exposure, a period like human PPD, did not exert an adverse effect on the mammary gland development at the prepubertal phase or on chemically induced mammary tumorigenesis in adult F1 female rats.